Effects of Transcranial Direct Current Stimulation (tDCS) Over the Frontal Polar Area on Motor and Executive Functions in Parkinson’s Disease; A Pilot Study - Ishikuro, Koji; Dougu, Nobuhiro; Nukui, Takamasa; Yamamoto, Mamoru; Nakatsuji, Yuji; Kuroda, Satoshi; Matsushita, Isao; Nishimaru, Hiroshi; Araujo, Mariana F. P.; Nishijo, Hisao (Frontiers in Aging Neuroscience, 2018)
Parkinson’s disease (PD) is a neurodegenerative disorder with motor and non-motor symptoms due to degeneration of dopaminergic neurons. The current pharmacological treatments induce complications associated with long-term use. However, current stimulation techniques for PD treatment, such as deep brain stimulation, are too invasive. In this context, non-invasive brain stimulation including transcranial direct current stimulation (tDCS) may be a safe and effective alternative treatment for PD. We previously reported that anodal tDCS over the frontal polar area (FPA) improved motor functions in heathy subjects. Therefore, in the present study, effects of tDCS over the FPA on motor and cognitive functions of PD patients were analyzed. Nine PD patients (three men and six women) participated in this cross over study with 3 tDCS protocols; anodal, cathodal, or sham tDCS over the FPA. Each tDCS protocol was applied for 1 week (5 times/week). Before and after each protocol, motor and cognitive functions of the patients were assessed using Unified Parkinson's Disease Rating Scale [UPDRS (part Ⅲ: motor examination)], Fugl Meyer Assessment set (FMA), Simple Test for Evaluating hand Function (STEF), and Trail Making Test A (TMT-A). The results indicated that anodal stimulation significantly decreased scores of motor disability in UPDRS-III compared with sham and cathodal stimulation, and significantly increased scores of motor functions in FMA compared with sham stimulation. Furthermore, anodal stimulation significantly decreased time to complete a motor task requiring high dexterity in STEF compared with those requiring low and medium levels of dexterity. In addition, anodal stimulation significantly decreased time to complete the TMT-A task, which requires executive functions, compared with sham stimulation. To the best of our knowledge, this is the first clinical research reporting that tDCS over the FPA successfully improved the motor and non-motor functions in PD patients. These findings suggest that tDCS over the FPA might be a useful alternative for the treatment of PD patients.